Authentic Deed Not Signed By The Parties Before A Notary (Simulated Case Of Land Acquisition Through A Deed Of Release Of Rights In Tabanan District, Tabanan Regency, Bali Province) - Kuncoro, Muhammad Aldo Britano (Jurnal Indonesia Sosial Sains, 2025)
The release of land rights, intended to sever the legal relationship between the rights holder and the land they possess, is carried out through a Deed of Release of Rights. Such an authentic deed must be drawn up before a notary, read aloud, and signed by the appearing parties, witnesses, and the notary themselves, as stipulated in the applicable laws and regulations. However, in reality, cases have been found that do not adhere to these provisions, specifically the case in Decision No. 144/PDT/2021 of the Denpasar High Court, where a Deed of Release of Rights prepared by a notary was not signed by the appearing parties in the presence of the public official who drew up the deed. Therefore, this research was conducted by addressing the issues related to the legal consequences of a Deed of Release of Rights not signed by the appearing party before a notary and the responsibility of a notary who prepares such a deed. This doctrinal research collects secondary data through document studies. The data, in the form of legal materials, is also strengthened by interviews with relevant sources and subsequently analyzed qualitatively. From the analysis, it can be explained that a Deed of Release of Rights not signed by the appearing party before a notary is degraded into a private deed (underhand deed) because the deed is declared legally defective, thus it cannot serve as a basis for the transfer of land rights. Thus, it can be stated that the creation of such a deed has caused losses to the parties, so a notary who prepares such a Deed of Release of Rights can be given sanctions, either administratively (ranging from a warning to dishonorable discharge based on Article 16 paragraph (11) of the Notary Law), or held civilly liable through a claim for damages as regulated in Article 1366 of the Civil Code. Furthermore, there is potential for criminal sanctions if it meets the elements specified in Articles 263, 264, and 266 of the Criminal Code concerning document forgery.